Prodrug strategies for targeted therapy triggered by reactive oxygen species - Peiró Cadahía, Jorge (Medchemcomm, 2019)
Increased levels of reactive oxygen species (ROS) have been associated with numerous pathophysiological conditions including cancer and inflammation and the ROS stimulus constitutes a potential trigger for drug delivery strategies. Over the past decade, a number of ROS-sensitive functionalities have been identified with the purpose of introducing disease-targeting properties into small molecule drugs – a prodrug strategy that offers a promising approach for increasing the selectivity and efficacy of treatments. This review will provide an overview of the ROS-responsive prodrugs developed to date. A discussion on the current progress and limitations is provided along with a reflection on the unanswered questions that need to be addressed in order to advance this novel approach to the clinic.